The Role of FSHR SNPs and AMH in Follicular Fluid and Serum in Ovarian Response during COS: A Pilot Study - Anagnostou, Elli; Mavrogianni, Despina; Prifti, Ilectra-Niki; Dimitroulia, Evangelia; Protopapas, Athanasios; Drakakis, Peter; Loutradis, Dimitrios (International Journal of Reproductive Medicine, 2021)
Background. Several studies have investigated on the polymorphism Ser680Asn of FSHR and its use as a predictive indicator of response to an IVF/ICSI protocol. Furthermore, measurement of AMH in serum and follicular fluid is a useful prognostic indicator for the outcome of an assisted reproduction attempt. The purpose of this study is to examine the FSH receptor Ser680Asn polymorphism in combination with AMH levels in both serum and follicular fluid, on the day of oocyte collection. Materials and Methods. A total of 32 women who underwent IVF/ICSI were included. Women were grouped into 2 groups: those who received rFSH (n=11) and those who received hMG (n=21). Serum AMH was measured on day 3 of the cycle, and AMH in the follicular fluid on the day of oocyte retrieval; the same day peripheral blood was collected for the genotyping of Ser680Asn. Results. No statistical significant difference was found between serum AMH and follicular fluid AMH regarding the FSH receptor genotype for the Ser680Asn polymorphism. Regarding the sAMH/ffAMH ratio in the 3 genotypes, the value was lower in Asn/Asn women than Ser/Ser and Ser/Asn, but no statistical difference was obtained. Women who carry the Ser allele have a higher number of follicles, retrieved oocytes, and mature oocytes than women who do not contain the Ser allele. Women with AMH<2.22 ng/ml presented lower AMH follicular fluid levels and lower serum AMH/follicular fluid AMH ratio in a statistically significant manner. Concerning the genotype for the polymorphism Ser680Asn of FSHR in relation to AMH levels, no statistically significant differences were found. Conclusions. The identification of polymorphisms, such as Ser680Asn of FSHR, along with the determination of endocrine markers in the follicular fluid, such as AMH, could lead at some point, to the personalized therapy setting per woman.